Antibodies to Porphyromonas gingivalis Indicate Interaction Between Oral Infection, Smoking, and Risk Genes in Rheumatoid Arthritis Etiology. Issue 3 (March 2016) - Kharlamova, Nastya; Jiang, Xia; Sherina, Natalia; Potempa, Barbara; Israelsson, Lena; Quirke, Anne‐Marie; Eriksson, Kaja; Yucel‐Lindberg, Tülay; Venables, Patrick J.; Potempa, Jan; Alfredsson, Lars; Lundberg, Karin
Abstract : Objective: To investigate the role of the periodontal pathogen Porphyromonas gingivalis in the etiology of rheumatoid arthritis (RA) by analyzing the antibody response to the P gingivalis virulence factor arginine gingipain type B (RgpB) in relation to anti–citrullinated protein antibodies (ACPAs), smoking, and HLA–DRB1 shared epitope (SE) alleles in patients with periodontitis, patients with RA, and controls. Methods: Anti‐RgpB IgG was measured by enzyme‐linked immunosorbent assay in 65 periodontitis patients and 59 controls without periodontitis, and in 1, 974 RA patients and 377 controls without RA from the Swedish population‐based case–control Epidemiological Investigation of Rheumatoid Arthritis (EIRA) study. Autoantibody status, smoking habits, and genetic data were retrieved from the EIRA database. Differences in antibody levels were examined using the Mann‐Whitney U test. Unconditional logistic regression was used to calculate odds ratios (ORs) with 95% confidence intervals (95% CIs) for the association of anti‐RgpB IgG with different subsets of RA patients. Results: Anti‐RgpB antibody levels were significantly elevated in periodontitis patients compared to controls without periodontitis, in RA patients compared to controls without RA, and in ACPA‐positive RA patients compared to ACPA‐negative RA patients. There was a significant association between anti‐RgpB IgG and RA (OR 2.96 [95% CI 2.00, 4.37]), which was even stronger than the association between smoking and RA (OR 1.37 [95% CI 1.07, 1.74]), and in ACPA‐positive RA there were interactions between anti‐RgpB antibodies and both smoking and the HLA–DRB1 SE. Conclusion: Our study suggests that the previously reported link between periodontitis and RA could be accounted for by P gingivalis infection, and we conclude that P gingivalis is a credible candidate for triggering and/or driving autoimmunity and autoimmune disease in a subset of RA patients.